O-037 MRI-Guided Sclerotherapy for Intraorbital Vascular Malformations: An Updated Experience. (29th July 2016) - Nicholson, A; Powell, T; Saunders, J; Hayek, B; Wojno, T; Nour, S
Abstract : Introduction/purpose: Despite benign histology, many congenital intra-orbital lesions have an aggressive prognosis owing to the confined orbital space and the intimate optic nerve association – resulting in pain, disfigurement, and vision loss. Complete surgical excision while preserving function may not be possible 1 The use of conventional fluoroscopically guided interventions is limited due to inability to visualize soft tissue anatomy. We have previously presented our work evaluating the feasibility of applying interventional MRI technology to access and treat these challenging intraorbital lesions, and now present an update with new patients and multi-year follow up. Materials and methods: Ten MRI-guided sclerotherapy procedures were performed on 4 patients (4M, 0F, age = 3–30y) presenting with cystic congenital intraorbital lesions. Patients presented with proptosis (n = 3), visual impairment (n = 2), diplopia (n = 1), ecchymosis (n = 2), and/or pain (n = 1). All procedures were exclusively performed within an interventional MRI suite with an in-room monitor used for real-time needle guidance, injection monitoring and bedside scanner operation. A 22 g MR-compatible needle was inserted into the targeted lesions under "MR-fluoroscopy" using triorthogonal image plane guidance 2 to interactively monitor the needle on continuously updated sets of true-FISP images (TR/TE, 4.35/2.18; FA, 60°; NSA, 3; TA, 3.11 s/slice). 0.6% gadolinium was mixed with 5% Ethanolamine Oleate (Ethamolin®) (0.15 ml:1.0 ml vol.) and injected under real-time monitoring using a triorthogonal FLASH sequence (TR/TE, 2484/5.4). Follow up on the earliest patients is available for three years. Results: Intra-orbital needle insertion and subsequent repositioning were sucesfully performed in all cases. The flexibility of triorthogonal guidance was most helpful in accessing the intraconal retrobulbar space. Active monitoring of sclerosing agent was persistently achieved on 3 planes. Targeted lesions ranged between 1.5 and 4 cm. Three lesions encircled/abutted the optic nerve. Between 1–5.5 mls of sclerosing material were injected per procedure. The smallest lesion was completely filled with sclerosant during each of 2 treatment sessions, with 3 partially filled to avoid excessive intraorbital pressure. Local edema and bruising were a standard finding for 1–2 weeks afterwards. Complete imaging resolution of one lymphatic malformation occurred. The 3 other lesions significantly shrank, without delayed complications. Conclusion: This report demonstrates long term success in using MRI technology to treat congenital intraorbital lesions, with no long term or delayed complications to date. This offers a new avenue for those patients who are typically deprived of surgical and other conventional interventional options. References: 1 Chung EM, et al . Radiographics 2007;(27 ):1777–799. 2 Derakhshan JJ, et al . Proc ISMRM 15 :487 (2007). Disclosures: A. Nicholson: None. T. Powell: None. J. Saunders: None. B. Hayek: None. T. Wojno: None. S. Nour: None.